2021
DOI: 10.24093/awej/covid.28
|View full text |Cite
|
Sign up to set email alerts
|

Female Saudi University Students’ Perceptions of Online Education Amid COVID-19 Pandemic

Abstract: The outbreak of the COVID-19 pandemic has wreaked havoc and caused world-wide disruptions to daily activities, including education. Numerous mitigation measures were taken to slow down the rapid spread of this pandemic. The situation, subsequently, entailed utilizing technology to ensure the continuation of the educational process. The abrupt shift to online education presented significant challenges to teachers and learners alike. Uncovering students’ perceptions of their online education experience will help… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The digital space appears to be a safe space for students who are often invisible in the face-to-face situation. Introvert students are more at ease to participate and interact digitally (Altuwairesh, 2021). This is also true for students who come from a teacher-centred culture (Ho et al, 2021).…”
Section: Higher Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…The digital space appears to be a safe space for students who are often invisible in the face-to-face situation. Introvert students are more at ease to participate and interact digitally (Altuwairesh, 2021). This is also true for students who come from a teacher-centred culture (Ho et al, 2021).…”
Section: Higher Educationmentioning
confidence: 99%
“…Within the student-centred approach, flexibility and consideration for students, and ways of learning, is key (Al-Nofaie, 2020). Important that lecturers vary teaching styles, also in the online environment, to accommodate diversity (Altuwairesh, 2021).…”
Section: Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, many studies have looked at the views of various stakeholders related to online learning. Second, inside the Kingdom of Saudi Arabia, Nasrin Altuwairesh [18] studied the perceptions of 241 female Saudi students at the University of King Saud of online teaching during the COVID-19 pandemic. She revealed that many of the students conveniently enjoyed their online experience and participated in online discussions.…”
Section: Literature Reviewmentioning
confidence: 99%